Effect of exposure time of pregnant females guppies, Poecilia reticulata Peters, in 17a-methyltestosterone solution on sex ratio of their offsprings - Junior, M. Zairin; Yunianti, A.; Dewi, R.R.S.P.S.; Sumawidjaja, Kusman (Jurnal Akuakultur Indonesia, 2002)
ABSTRACTThis experiment was carried out to study the effect of female broodstocks immersion in 17amethyltestosterone (MT) solution on sex ratio of their offspring, Three-months old males and females were paired to mate in aquaria for four days.  Broodstocks were fed with frozen blood worm and water flea 2-3 tii-nes daily.  Twelve days after mating, female broodstock were treated by immersing in 2 mg/1 MT solution for 0. 6, 12, 24 and 48 hours.  Birthed guppy babies were collected and reared separately from their parents.  During the rearing period, the babies were fed with artemia nauplius and silkworm until identification for male and female.  Percentage of female offspring in control group were higher than those of male.  Exposure of pregnant females to MT solution for 0, 6, 12, 24, and 48 hours resulted in 42, 1'/o, 51%, 84,6%, 1 00%, dan 100% of males offspring, respectively.  The best result was obtained from 24 hours treatment.  Longer treatment duration tend to shorten time interval between treatment and birth. Key words :  Guppy, 17(x-methyltestosterone, exposure time, broodstock immersion, sex ratio   ABSTRAK Penefitian ini bertuiuan untuk mengetahui pengaruh lama waktu perendaman induk di dalam larutan hormon 17a-metiltestosteron (MT) terhadap nisbah kelamin ikan gapi.  Induk Ikan gapi berumur tiga bulan dikawinkan berpasangan di dalam akuarium selama empat hari Induk diberi pakan cuk merah beku dan kutu air dengan frekuensi 2-3 kali sehari.  Dua belas hari setelah masa perkawinan, induk betina diberi perlakuan berupa perendaman di dalam larutan MT 2 mg/1 selama 0 (kontrol), 6, 12, 24, dan 48 jam.  Anak-anak ikan gapi yang baru lahir dipelihara terpisah dari induknya.  Selama masa pemeliharaan, anak ikan gapi diberi pakan nauplius artemia dan cacing rambut.  Pemeliharaan berlangsung sampai jenis kelamin anak ikan gapi dapat diidentifikasi.  Persentase anak ikan gapi betina pada semua ulangan kontrol lebih tinggi daripada .iantan dengan perbandingan persentase rata-rata 57,9%: 42,1%.  Adapun pada lama waktu perendaman 0, 6, 12, 24, dan 48 jam, menghasilkan persentase anak ikan gapi berfenotip jantan berturut-turut sebesar 42,1%, 51%, 84,6%, 100%, dan 100%.  Lama waktu perendaman terbaik adalah 24 jam.  Selain itu terdapat kecenderungan bahwa semakin lama waktu perendaman semakin cepat kelahirannya. Kata kunci :  Ikan gapi, 17ot-metiltestosteron, lama perendaman, perendaman induk, nisbah kelamin